Efficacy and safety of Bufei Huoxue capsules in the treatment of stable COPD: A multicenter, double-blind, placebo-controlled, randomized clinical trial - Yuqin Chen; Bihua Zhong; Zhiwan Wang; Lei Xu; Zhe Cheng; Wenjun He; Jingjing Qi; Yinji Xu; Xiaoying Huang; Li Li; Minfang Li; Yingyun Fu; et al. (Pharmacological Research - Modern Chinese Medicine, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory condition characterized by irreversible airflow limitation, resulting in significant morbidity and mortality. Bufei Huoxue capsules (BFHX) have demonstrated potential benefits in small-scale clinical studies, including the improvement of cardiopulmonary function, reduction of blood viscosity, and enhancement of immune responses. These findings support the promise of BFHX for COPD treatment. Therefore, large-scale, standardized, multicenter clinical trials are urgently needed to validate these results. Methods: Patients with stable COPD who met the inclusion and exclusion criteria were recruited. BFHX or placebo was given orally three times a day (1.4 g/dose) for 12 months. The primary outcome was the 6 min walk distance (6MWD). Results: Among 208 patients (one patient did not receive the placebo) with COPD, 154 successfully completed the study, including 83 patients in the BFHX group and 71 patients in the placebo group. 6MWD tended to increase in the BFHX group and decrease in the placebo group. After 9 and 12 months of treatment, the improvement in 6MWD compared with baseline was significantly better in the BFHX group than in the placebo group (full analysis set after 9 months: 36.81 ± 8.06 m vs. −12.11 ± 8.41 m; 95 % confidence interval = 25.50–72.34; p < 0.0001. full analysis set after 12 months: 36.65 ± 8.47 m vs. −18.24 ± 9.26 m; 95 % confidence interval = 29.82–79.96; p < 0.0001). Furthermore, BFHX effectively alleviated fatigue, dyspnea, coughing, and sputum in patients with stable COPD while improving their quality of life and pulmonary function. Discussion: BFHX administration significantly enhanced exercise tolerance in patients with stable COPD, alleviated fatigue and dyspnea, improved pulmonary function, ameliorated cough and sputum production, and enhanced overall quality of life. Moreover, the safety profile of BFHX was commendable, making it a demonstrating potential therapeutic value. Trial registration: The China Clinical Trial Registry (ID: ChiCTR1800016955)